Enantioselective synthesis of phosphine boranes via crystallization‐induced dynamic resolution of lithiated intermediate by understanding the underlying epimerization process - Kuzu, Mehmet Yasin; Schmidt, Annika; Strohmann, Carsten (Wiley, 2024)
Described herein is the successful crystallization-induced dynamic resolution (CIDR) of an α-lithiated phosphine borane utilizing the easily accessible and inexpensive ligand (R,R)-TMCDA. Starting from the essential P-prochiral building block dimethyl phenyl phosphine borane we were able to obtain phosphine boranes in yields up to 80 % and e.r. up to 98 : 2 by crystallization of the lithiated intermediate prior to the trapping reaction. NMR-based deuterium labeling experiments indicate that the epimerization in solution is based on the intermolecular proton transfer between nonlithiated phosphine borane and the corresponding lithiated intermediate, rendering the presence of the remaining starting compound in an optimized solvent mixture the main factor for successful enantioselective synthesis. Quantum chemical calculations using different model systems based on solid state structures confirm these experimental results. By gaining insights into the epimerization mechanism, essential principles for CIDR of lithiated phosphine boranes are elucidated that may be expanded to other important P-stereogenic compounds and simple chiral amines.
Angewandte Chemie International Edition; 63(19)
Keywords: Asymmetric synthesis; Chiral resolution; Dynamic interconversion; Lithiated intermediate; Phosphine boranes; 540